2017
DOI: 10.5539/jas.v9n11p154
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Toxicity from Seed-Treated Cotton on Bees and Pollen Collection Capacity

Abstract: Apis mellifera bees that forage in agricultural fields may be exposed to pesticides through many routes. One of them is the collection of pollen contaminated with insecticides. In this study, we evaluate the mortality of adult honeybees exposed to pollen from cotton plants whose seeds were treated with insecticides thiamethoxam, clothianidin, imidacloprid and fipronil, and the pollen collection capacity of adult honeybees in cotton fields. Bee mortality based on linear regression analysis showed significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Imidacloprid residue in corn plants was 6.6 ppb in the flowers and 2.1 ppb in pollen, when corn seeds were treated @ 0.7 mg kg −1 of seed 19 . However, De Souza et al 20 . found that A. mellifera mortality was not affected by the pollen from cotton plant grown from seed treated with thiamethoxam, clothianidin, imidacloprid and fipronil.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Imidacloprid residue in corn plants was 6.6 ppb in the flowers and 2.1 ppb in pollen, when corn seeds were treated @ 0.7 mg kg −1 of seed 19 . However, De Souza et al 20 . found that A. mellifera mortality was not affected by the pollen from cotton plant grown from seed treated with thiamethoxam, clothianidin, imidacloprid and fipronil.…”
Section: Resultsmentioning
confidence: 96%
“…Imidacloprid residue in corn plants was 6.6 ppb in the flowers and 2.1 ppb in pollen, when corn seeds were treated @ 0.7 mg kg −1 of seed. 19 However, De Souza et al 20 found that A. mellifera mortality was not affected by the pollen from cotton plant grown from seed treated with thiamethoxam, clothianidin, imidacloprid and fipronil. Goulson, 21 reported that a dose of 1 g pollen and 2.6 mL nectar is required to be consumed by honey bees to obtain an oral median lethal concentration (LC 50 ) value of 5 ng bee −1 for imidacloprid, 7 which could get accumulated inside the body over a number of days or weeks.…”
Section: Dissipation Kinetics Of Imidacloprid Residue After Seed Trea...mentioning
confidence: 99%
“…These systemic products circulate throughout parts of the plants and are applied to seeds before sowing or are absorbed by plants from residues in the soil (BONMATIN et al, 2015). Although they are necessary to prevent pest damage, pollinators can also be exposed to their residues while foraging in treated crops (SIMON-DELSO et al, 2015), such as soybeans.…”
Section: Abstract: Mortality; Neonicotinoids; Fipronilmentioning
confidence: 99%